Paralytic Toxin Producing Dinoflagellates in Latin America: Ecology and Physiology - Band-Schmidt, Christine J.; Durán-Riveroll, Lorena M.; Bustillos-Guzmán, José J.; Leyva-Valencia, Ignacio; López-Cortés, David J.; Núñez-Vázquez, Erick J.; Hernández-Sandoval, Francisco E.; Ramírez-Rodríguez, Dulce V. (Frontiers in Marine Science, 2019)
In this review we summarize the current state of knowledge regarding taxonomy, bloom dynamics, toxicity, autoecology, and trophic interactions, of saxitoxin producing dinoflagellates in this region. The dinoflagellates Gymnodinium catenatum, Pyrodinium bahamense and several species of Alexandrium are saxitoxin producers, and have been responsible of paralytic shellfish poisoning in different regions of Latin America, causing intoxications and important fisheries losses. The species distribution differ; most harmful algal blooms of G. catenatum are from the northern region, however this species has also been reported in central and southern regions. Blooms of P. bahamense are mostly reported in North and Central America, while blooms of Alexandrium species are more common in South America, however this genus is widely spread in Latin America. Species and regional differences are contrasted, with the aim to contribute to future guidelines for an international scientific approach for research and monitoring activities that are needed to increase our understanding of paralytic toxin producing dinoflagellates in this region.